Method for copolymerization synthesis of triazinyl carbon nitride photocatalyst
By using guanidine hydrochloride and sodium thiocyanate as comonomers, the structural defects of triazine-based carbon nitride photocatalysts are accurately controlled, and the problem of low photocatalytic efficiency caused by structural defects in the prior art is solved, and high efficiency is achieved photocatalytic decomposition of water to produce hydrogen.
Patent Information
- Application Number
- CN202411579873.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-11-07
AI Technical Summary
The existing triazine-based carbon nitride photocatalysts have a large number of structural defects during the synthesis process, which hinder the migration and separation capabilities of photogenerated carriers and lead to inefficient photocatalytic decomposition of water.
Using nitrogen-rich guanidine hydrochloride and nitrogen-deficient sodium thiocyanate as comonomers, the structural defect type and concentration of triazine-based carbon nitride polymers are accurately controlled, the melting temperature is reduced and the ammonia removal is optimized. dynamics.
By precisely controlling structural defects, the separation and migration characteristics of photogenerated carriers are improved, the efficiency of photocatalytic reactions is enhanced, and efficient photocatalytic full decomposition of water is achieved.
Smart Images

Figure CN119406441A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of photocatalytic water decomposition, and specifically relates to a copolymerization synthesis method of a triazine-based carbon nitride photocatalyst and its application in photocatalytic full water decomposition to produce hydrogen. Background Art
[0002] Photocatalytic water splitting technology is the process in which a catalyst converts water into hydrogen (H2) and oxygen (O2) under light conditions. It is a mild, green and environmentally friendly method of hydrogen production. It is a potential solution for solar hydrogen production and is of great significance for my country to achieve the goals of "carbon peak and carbon neutrality".
[0003] Photocatalytic water splitting to produce hydrogen is an uphill reaction with an increase in Gibbs free energy (∆G = +237 kJ·mol –1 ), the premise for effectively promoting the reaction is to ensure that the photogenerated carriers are effectively separated and migrated to the surface active sites of the catalyst before recombination. However, the large number of defect structures in the catalyst not only hinder the migration and separation of photogenerated carriers, but also are accompanied by inevitable energy loss, which largely restricts the efficiency of converting solar energy into hydrogen energy. Therefore, the key to developing efficient semiconductor catalysts for photocatalytic water splitting is to rationally control various structural defects and improve the crystallinity of the catalyst.
[0004] Carbon nitride photocatalysts are composed of triazine or heptazine subunits. They have the advantages of high chemical stability, non-biotoxicity, suitable energy band structure, and simple synthesis. They have been widely used in the field of photocatalytic water decomposition to produce hydrogen. However, in the traditional solvent thermal or solid phase synthesis routes, the inherent flexibility of the carbon-based π-conjugated skeleton in carbon nitride materials leads to the formation of a large number of natural structural defects, which is not conducive to the photocatalytic reaction. The latest research shows that in the presence of molten salt, highly condensed and structurally ordered triazine-based carbon nitride polymers can be synthesized by ion thermal synthesis, and their defect density is greatly reduced. However, the condensation process of triazine-based carbon nitride involves multi-step deamination, and the deamination kinetics of the polymerization reaction cannot be precisely controlled using a single precursor. In addition, the high melting point of the traditional condensation system limits the precursor mass transfer rate by convection and diffusion, which inevitably leads to the formation of a large number of carbon atom vacancies (V C ) defects. At the same time, the uneven heat distribution in the high-melting-point polymerization system may cause the conjugated skeleton to exceed its stability limit, triggering irreversible local carbonization, thereby generating nitrogen atom vacancies (V N ) defects. These complex structural defects seriously hinder the effective utilization of photogenerated charges and reduce the efficiency of photocatalytic water splitting. Therefore, developing a controllable and efficient synthesis method for triazine-based carbon nitride polymers and accurately controlling harmful structural defects in polymers remain the focus and difficulty of current research. Summary of the invention
[0005] The purpose of the present invention is to provide a method for controlling and efficiently synthesizing triazine-based carbon nitride polymers and accurately controlling their structural defects in view of the shortcomings of the prior art.
[0006] To achieve the above object, the present invention adopts the following technical solution: A method for copolymerizing a triazine-based carbon nitride photocatalyst comprises the following steps: 1) nitrogen-rich guanidine hydrochloride, nitrogen-deficient sodium thiocyanate and lithium chloride are mixed in proportion and then heat treated to obtain polymer carbon nitride mixed with molten salt; 2) The ampoule containing the polymer carbon nitride is evacuated and sealed, and heat-treated again to obtain triazine carbon nitride; 3) The obtained triazine carbon nitride is dispersed in deionized water for washing, filtered to remove residual salt, and then placed in a vacuum oven for drying to obtain a milky white powder product.
[0007] Furthermore, the mass ratio of guanidine hydrochloride, sodium thiocyanate and lithium chloride used in step 1) is 1:0:1-1:3:1.
[0008] Furthermore, the heat treatment temperature in step 1) is 300-500°C, the holding time is 2-8 h, and the heating rate is 1-6°C / min.
[0009] Furthermore, the heat treatment temperature in step 2) is 500-600°C, the holding time is 6-12 h, and the heating rate is 1-6°C / min.
[0010] Furthermore, in step 3), the drying temperature is 60° C. and the drying time is 3 h.
[0011] The present invention mainly utilizes two complementary comonomers, namely nitrogen-rich guanidine hydrochloride and nitrogen-deficient sodium thiocyanate, to reduce the melting temperature of the polymerization system and optimize the deamination kinetics of carbon nitride, thereby synthesizing a triazine-based carbon nitride polymer photocatalyst. In the process, by controlling the stoichiometric relationship of the two comonomers, the type and concentration of structural defects in the triazine-based carbon nitride can be accurately adjusted, thereby improving the separation and migration characteristics of photogenerated carriers and improving the catalytic reaction efficiency. Therefore, the prepared triazine-based carbon nitride photocatalyst can be used for photocatalytic water decomposition to produce hydrogen.
[0012] Furthermore, the method specifically comprises using pure water as a reactant to load CoO on the surface of the triazine-based carbon nitride photocatalyst by an in-situ photodeposition method. x and Rh-Cr2O3 as co-catalysts to achieve photocatalytic decomposition of water into hydrogen and oxygen.
[0013] Furthermore, CoO xThe loading amounts of Rh-Cr2O3 and Rh-Cr2O3 were both 0.05-1 wt%.
[0014] Compared with the prior art, the present invention has the following advantages: (1) The present invention provides a copolymerization synthesis method of a triazine-based carbon nitride photocatalyst and applies it to the photocatalytic water splitting reaction. It uses two complementary copolymer monomers, namely nitrogen-rich guanidine hydrochloride and nitrogen-deficient sodium thiocyanate, to reduce the melting temperature of the polymerization system, optimize the condensation reaction kinetics, and achieve precise control of structural defects, promote the separation and migration of photogenerated carriers, and improve the utilization efficiency of photogenerated carriers, thereby improving the catalytic reaction efficiency.
[0015] (2) The catalyst preparation process of the present invention is simple, low-cost and highly accurate. The catalytic reaction conditions are mild and environmentally friendly, which is conducive to large-scale industrial production and application, and is of great significance for ensuring energy security and achieving "carbon peak and carbon neutrality". BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is a diagram of the copolymerization mechanism of guanidine hydrochloride and sodium thiocyanate at the molecular level in Example 2.
[0017] Figure 2 The XRD pattern of the triazine carbon nitride prepared in Example 1-3.
[0018] Figure 3 This is the Fourier infrared spectrum of the triazine carbon nitride prepared in Example 1-3.
[0019] Figure 4 This is the electron spin resonance spectrum of the triazine carbon nitride prepared in Example 1-3.
[0020] Figure 5 Elemental analysis results of triazine carbon nitride prepared in Examples 1-3.
[0021] Figure 6 This is a scanning electron microscope image of the triazine carbon nitride prepared in Example 2.
[0022] Figure 7 The morphological changes of samples using the raw materials used in Example 2 and guanidine thiocyanate as a nitrogen-containing precursor and molten salt for heat treatment at 300°C and nitrogen conditions.
[0023] Figure 8 This is a comparison chart of the activity of triazine-based carbon nitride prepared in Examples 1-3 for photocatalytic water decomposition. DETAILED DESCRIPTION
[0024] A method for copolymerizing triazine-based carbon nitride photocatalyst comprises the following steps: 1) Guanidine hydrochloride, sodium thiocyanate and lithium chloride are mixed in a mass ratio of 1:0:1-1:3:1 and placed in an ampoule, and heat treated at 300-500°C for 2-8 h (heating rate of 1-6°C / min) to obtain polymer carbon nitride mixed with molten salt; 2) The ampoule containing the polymer carbon nitride is evacuated and sealed, and then heat treated at 500-600°C for 6-12 h (heating rate of 1-6°C / min) to obtain triazine carbon nitride; 3) The obtained triazine carbon nitride was dispersed in deionized water for washing, filtered to remove residual salt, and then placed in a vacuum oven and dried at 60° C. for 3 h to obtain a milky white powder product.
[0025] In order to make the contents of the present invention easier to understand, the technical solution of the present invention is further described below in conjunction with specific implementation methods, but the present invention is not limited thereto.
[0026] Example 1 The nitrogen-rich guanidine hydrochloride, nitrogen-deficient sodium thiocyanate and lithium chloride were fully mixed in a mass ratio of 1:0:1 and placed in an ampoule. The temperature was raised to 400 °C at a rate of 2 °C / min. After 4 hours of constant temperature, a solid powder A of a mixture of polymer carbon nitride and molten salt was obtained. The ampoule containing solid powder A was evacuated and sealed, and calcined at 550 °C for 12 hours (heating rate of 1 °C / min) to obtain a solid powder B of a mixture of triazine-based carbon nitride material and molten salt. After natural cooling, the solid powder B was washed with deionized water, filtered, and the residual salt was removed to obtain a white solid powder of triazine-based carbon nitride material C. It was dried in a vacuum oven at 60 °C for 3 hours to obtain a white powder product, namely, a triazine-based carbon nitride material.
[0027] Example 2 The nitrogen-rich guanidine hydrochloride, nitrogen-deficient sodium thiocyanate and lithium chloride were fully mixed in a mass ratio of 1:0.5:1 and placed in an ampoule. The temperature was raised to 400 °C at a rate of 2 °C / min. After 4 hours of constant temperature, a solid powder A of a mixture of polymer carbon nitride and molten salt was obtained. The ampoule containing solid powder A was evacuated and sealed, and calcined at 550 °C for 12 hours (heating rate of 1 °C / min) to obtain a solid powder B of a mixture of triazine-based carbon nitride material and molten salt. After natural cooling, the solid powder B was washed with deionized water, filtered, and the residual salt was removed to obtain a white solid powder of triazine-based carbon nitride material C. It was dried in a vacuum oven at 60 °C for 3 hours to obtain a white powder product, namely, a triazine-based carbon nitride material.
[0028] Example 3 The nitrogen-rich guanidine hydrochloride, nitrogen-deficient sodium thiocyanate and lithium chloride were fully mixed in a mass ratio of 1:1:1 and placed in an ampoule. The temperature was raised to 400 °C at a rate of 2 °C / min. After 4 hours of constant temperature, a solid powder A of a mixture of polymer carbon nitride and molten salt was obtained. The ampoule containing solid powder A was evacuated and sealed, and calcined at 550 °C for 12 hours (heating rate of 1 °C / min) to obtain a solid powder B of a mixture of triazine-based carbon nitride material and molten salt. After natural cooling, the solid powder B was washed with deionized water, filtered, and the residual salt was removed to obtain a white solid powder of triazine-based carbon nitride material C. It was dried in a vacuum oven at 60 °C for 3 hours to obtain a white powder product, namely, a triazine-based carbon nitride material.
[0029] Full water decomposition activity experiment: In order to evaluate the activity of the triazine-based carbon nitride sample prepared in Example 1, CoO was loaded on its surface by in situ photodeposition. x and Rh-Cr2O3 as oxygen- and hydrogen-producing co-catalysts for light-driven water splitting reactions.
[0030] The photocatalytic reaction is carried out in a reaction vessel connected to a closed gas circulation system, and the hydrogen content released is measured by gas chromatography. The specific operation steps are as follows: before the reaction, an aqueous solution containing Co(NO3)2·6H2O, RhCl3·3H2O and K2CrO4 is prepared as a co-catalyst precursor solution (Co 2+ , Rh 3+ The concentrations of Cr2O3 and Cr2O3 were both 3 mg·mL -1 ). Weigh 50 mg of triazine carbon nitride sample and add it to 100 mL of pure water. Pour it into the reactor and add 0.1 mL of the prepared co-catalyst precursor solution. Use the vacuum system to completely remove the air in the system. Turn on the xenon lamp (300 W) for irradiation under continuous stirring (the system temperature is maintained at 15°C), and use gas chromatography to analyze the released gas online (the gas chromatograph used is GC-8A from Shimadzu Corporation of Japan).
[0031] Figure 2 The XRD diagram of the triazine-based carbon nitride prepared in Examples 1 to 3. It can be found from the figure that all samples contain characteristic diffraction peaks of triazine-based carbon nitride, proving the successful synthesis of triazine-based carbon nitride. Among them, the diffraction intensity of the triazine-based carbon nitride synthesized in Example 2 is significantly improved, indicating that it has less structural defects and a high degree of structural order.
[0032] Figure 3 The Fourier transform infrared spectrum of the triazine carbon nitride prepared in Example 1-3 is shown in FIG. −1The strong peak at 1200-1600 cm -1 The absorption peak in the region can be attributed to the stretching vibration of the triazine ring, confirming that the prepared product is triazine-based carbon nitride.
[0033] Figure 4 The electron spin resonance spectra of the triazine-based carbon nitride prepared in Examples 1 to 3 are shown in FIG. As can be seen from the figure, the triazine-based carbon nitride synthesized in Example 1 has a characteristic carbon atom vacancy defect signal; no defect-related signal is detected in the triazine-based carbon nitride synthesized in Example 2, indicating that its polymerization degree is high; and the triazine-based carbon nitride synthesized in Example 3 of the present invention has a characteristic nitrogen atom vacancy defect signal.
[0034] Figure 5 This is the elemental analysis result of the triazine-based carbon nitride prepared in Examples 1-3. The theoretical C / N atomic ratio of the triazine-based carbon nitride polymer is 0.6667. It can be seen from the figure that the C / N atomic ratio of the triazine-based carbon nitride synthesized in Example 1 is lower than its theoretical value; the C / N atomic ratio of the triazine-based carbon nitride synthesized in Example 2 is approximately equal to its theoretical value; and the C / N atomic ratio of the triazine-based carbon nitride synthesized in Example 3 is higher than its theoretical value. Figure 4 It shows that the defect type and concentration in triazine carbon nitride crystals can be precisely controlled by adjusting the stoichiometric relationship of the precursors.
[0035] Figure 6 This is a scanning electron microscope image of the triazine-based carbon nitride prepared in Example 2. The image further proves that the synthesized triazine-based carbon nitride has a high degree of crystallinity.
[0036] Figure 7 The morphological changes of the samples using the raw materials used in Example 2 and guanidine thiocyanate as a nitrogen-containing precursor and molten salt for heat treatment at 300°C under nitrogen conditions are shown in the figure. As can be seen from the figure, compared with the strategy of using guanidine thiocyanate as a nitrogen-containing precursor and molten salt to prepare highly crystalline carbon nitride in existing reports, the mixture of guanidine hydrochloride, sodium thiocyanate and molten salt can be completely melted below 300°C, indicating that the method of copolymerizing guanidine hydrochloride and sodium thiocyanate can effectively reduce the melting temperature of the reaction system and promote the mass transfer rate of the reaction monomers.
[0037] Figure 8 The activity comparison diagram of the triazine-based carbon nitride prepared in Examples 1 to 3 for photocatalytic water decomposition is shown in the figure. The figure proves that by regulating the stoichiometric relationship of the two comonomers, the structural defects can be controlled, so that the triazine-based carbon nitride synthesized in Example 2 has high crystallinity and low defect density, and thus exhibits higher photocatalytic water decomposition performance.
[0038] The above embodiments are merely examples for clearly explaining the present invention, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above descriptions. It is not necessary and impossible to list all the implementation methods here, and the obvious changes or modifications derived therefrom are still within the protection scope of the present invention.
Claims
1. A method for copolymerizing triazine-based carbon nitride photocatalyst, characterized in that: The following steps are involved: 1) Guanidine hydrochloride, sodium thiocyanate and lithium chloride are mixed in proportion and then heat treated to obtain polymer carbon nitride mixed with molten salt; 2) The ampoule containing the polymer carbon nitride is evacuated and sealed, and heat-treated again to obtain triazine carbon nitride; 3) The obtained triazine carbon nitride is dispersed in deionized water for washing, filtering and drying to obtain a powder product.
2. The method according to claim 1, characterized in that The mass ratio of guanidine hydrochloride, sodium thiocyanate and lithium chloride used in step 1) is 1:0:1-1:3:
1.
3. The method according to claim 1, characterized in that The heat treatment temperature in step 1) is 300-500°C and the holding time is 2-8 h.
4. The method according to claim 1, characterized in that The heat treatment temperature in step 2) is 500-600°C and the holding time is 6-12 h.
5. An application of the triazine-based carbon nitride photocatalyst prepared by the method of claim 1 in photocatalytic water decomposition to produce hydrogen, characterized in that: The triazine-based carbon nitride photocatalyst can photocatalytically decompose water into hydrogen and oxygen in pure water.
Citation Information
Patent Citations
Method for preparation of water-soluble luminous graphite-phase carbon nitride nano kelp
CN105152147A
Crystalline-phase carbon nitride photocatalyst with ordered-twisted interface
CN115608402A
Triazinyl crystalline phase carbon nitride photocatalyst prepared from double precursors and application of triazinyl crystalline phase carbon nitride photocatalyst
CN116673058A
PHI / zinc oxide heterojunction photocatalyst as well as low-temperature synthesis method and application thereof
CN117619447A
Preparation method and application of polytriazinyl crystalline phase carbon nitride nanosheet
CN118062813A